Efficient Annihilation Electrochemiluminescence of Cationic Helicene Luminophores. Issue 7 (16th February 2017) - Li, Haidong; Voci, Silvia; Wallabregue, Antoine; Adam, Catherine; Labrador, Geraldine M.; Duwald, Romain; Hernández Delgado, Irene; Pascal, Simon; Bosson, Johann; Lacour, Jérôme; Bouffier, Laurent; Sojic, Neso
Abstract: The electrochemistry and annihilation electrochemiluminescence (ECL) of a series of chiral cationic helicene luminophores containing various substituents were investigated in acetonitrile solvent. The electrochemical characterization evidenced a systematic reversible reduction of cationic derivatives, whereas the oxidation could be reversible or not, depending on the nature of the core heteroatoms within the structure as well as the functional‐group appendages. One of the key parameters governing the ECL intensity is, indeed, the formal redox potentials for the electrogeneration of the neutral radical and dication radical species, which will undergo the annihilation reaction. On that basis, a thermodynamic wall of efficiency was proposed in the case of ECL annihilation pathway to predict the formation efficiency of the emitting excited state and, eventually, the light emission's strength. This very simple wall is constructed by plotting the difference of formal potentials in function of the fluorescence wavelength, thus delimiting two domains where ECL is thermodynamically possible or unfavorable. Abstract : Another brick in the ECL wall : A series of chiral cationic helicene luminophores jumps over the energetic electrochemiluminescence (ECL) wall.